Research on influencing factors and correlation pathways of rural teachers’ retention in China - Chen, Fang; Li, Ye-Jun; Liu, Tie-Fang (Frontiers in Psychology, 2026)
IntroductionTeacher retention in rural China remains a critical issue, with significant implications for educational equity and student achievement. Addressing the challenge of retaining qualified teachers in remote and economically underdeveloped regions is essential for ensuring high-quality education for rural students. This study investigates the factors influencing rural teacher retention and proposes a hierarchical model to elucidate their interrelationships.MethodsEmploying grounded theory and interpretive structural modeling (ISM), this study conducted semi-structured interviews with 33 rural teachers who had taught in rural areas for more than three years. The grounded theory approach was used to construct a theoretical model of factors influencing teacher retention, while ISM was applied to analyze the hierarchical relationships and interconnection pathways among these factors.ResultsThis study identifies multiple interrelated factors influencing the retention of rural teachers, constructs a hierarchical model, and reveals that teacher retention is jointly affected by foundational, transitional, and direct factors. The model highlights the complex interactive relationship between material conditions and psychological needs in teachers’ decisions to remain in rural education.DiscussionThe findings suggest that improving rural teacher retention requires a multifaceted approach that addresses both material and psychological needs. Social status, professional identity, and a sense of educational mission emerge as core driving forces behind teacher retention. The study challenges the notion that salary increases alone can universally resolve retention issues, emphasizing the importance of enhancing teachers’ social recognition, providing clear career development pathways, and fostering a supportive school environment. Differentiated retention strategies should be developed based on teachers’ gender, subject-specific characteristics, and family circumstances to better meet their distinct needs. These insights provide policymakers with a comprehensive theoretical foundation for designing more precise and effective intervention strategies to enhance rural teacher retention.